2013
DOI: 10.1111/jlme.12098
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Request Criterion in Jurisdictions Where Assisted Dying is Lawful? A Review of the Criteria and Evidence in the Netherlands, Belgium, Oregon, and Switzerland

Abstract: Some form of assisted dying (voluntary euthanasia and/or assisted suicide) is lawful in the Netherlands, Belgium, Oregon, and Switzerland. In order to be lawful in these jurisdictions, a valid request must precede the provision of assistance to die. Non-adherence to the criteria for valid requests for assisted dying may be a trigger for civil and/or criminal liability, as well as disciplinary sanctions where the assistor is a medical professional. In this article, we review the criteria and evidence in respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A recent review of adherence to request criteria in jurisdictions where assisted dying is lawful showed no evidence of exploitation in the 17 years assisted dying has been legal in Oregon. 16 If the UK's reason to hold back on legalising assisted dying in 2006 was lack of experience, one must now acknowledge this no longer holds true in light of this report. No calls have been made to extend the legislation to include non-voluntary or even voluntary euthanasia since 1997.…”
Section: Divided Opinionsmentioning
confidence: 96%
“…A recent review of adherence to request criteria in jurisdictions where assisted dying is lawful showed no evidence of exploitation in the 17 years assisted dying has been legal in Oregon. 16 If the UK's reason to hold back on legalising assisted dying in 2006 was lack of experience, one must now acknowledge this no longer holds true in light of this report. No calls have been made to extend the legislation to include non-voluntary or even voluntary euthanasia since 1997.…”
Section: Divided Opinionsmentioning
confidence: 96%
“…5 The criteria comprised the agreement of another doctor, the assessment of the patient's mental capacity and the presence of a terminal illness with less than six months to live. 24 Additional measures to ensure an informed and unforced decision involved adequate pain relief and access to end-of-life care. 25 Assisted dying proponents support that safeguards and regulations in place are very powerful since only one in 50 terminally ill patients have a discussion about the process with their doctor and even fewer complete it.…”
Section: Justicementioning
confidence: 99%
“…It has also been demonstrated that since the legalisation of euthanasia, PC has strongly expanded and prudence in decision-making and care at the end of life has improved. No substantial evidence of so-called practical “slippery slope” (van der Burg 1991 ) phenomena has been found (Bernheim et al 2008 ; Bernheim et al 2012 ; Chambaere et al 2010a ; Lewis and Black 2013 1 ), and Belgians’ confidence in their health care system, already high before the euthanasia legislation, further rose to the second-highest in Europe (European Values Study 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 The Lewis and Black ( 2013 ) article exhaustively reviews all extant data in “permissive” countries on reported cases of granted and refused assisted dying. Their aim is to investigate the degree of compliance with legal requirements for the validity of requests of assisted dying.…”
mentioning
confidence: 99%
See 1 more Smart Citation